1998
DOI: 10.1002/(sici)1096-9861(19980824)398:2<225::aid-cne5>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Critical assessment of the involvement of perforations, spinules, and spine branching in hippocampal synapse formation

Abstract: Several studies propose that long-term enhancement of synaptic transmission between neurons results from the enlargement, perforation, and splitting of synapses and dendritic spines. Unbiased analyses through serial electron microscopy were used to assess the morphological basis for synapse spilitting in hippocampal area CA1. Few perforated synapses and almost no split (i.e., branched) spines occurred at postnatal day 15, an age of high synaptogenesis; thus, synapse splitting is unlikely to be important during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
85
0

Year Published

2000
2000
2005
2005

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(102 citation statements)
references
References 55 publications
(70 reference statements)
17
85
0
Order By: Relevance
“…Initially, the synaptic junction was thought to enlarge, then develop a perforation, then split into two separate synaptic junctions within a single synaptic terminal and, finally, the spine itself would divide into two spines, each containing one synaptic junction. However, when Kristin Harris' group examined synapses carefully in CA1 of hippocampus using unbiased stereological techniques as applied to electron microscopy, they failed to observe a single branched ('multiple-headed' spine) with the different 'heads' in synaptic contact with the same presynaptic bouton (Sorra et al, 1998), an intermediate stage that is predicted by the splitting hypothesis. Subsequently, they examined the issue of spine splitting directly by serially reconstructing synapses on hippocampal dendrites and the surrounding neuropil across development and in response to hippocampal LTP (Fiala et al, 2002).…”
Section: Neuronal Plasticitymentioning
confidence: 99%
“…Initially, the synaptic junction was thought to enlarge, then develop a perforation, then split into two separate synaptic junctions within a single synaptic terminal and, finally, the spine itself would divide into two spines, each containing one synaptic junction. However, when Kristin Harris' group examined synapses carefully in CA1 of hippocampus using unbiased stereological techniques as applied to electron microscopy, they failed to observe a single branched ('multiple-headed' spine) with the different 'heads' in synaptic contact with the same presynaptic bouton (Sorra et al, 1998), an intermediate stage that is predicted by the splitting hypothesis. Subsequently, they examined the issue of spine splitting directly by serially reconstructing synapses on hippocampal dendrites and the surrounding neuropil across development and in response to hippocampal LTP (Fiala et al, 2002).…”
Section: Neuronal Plasticitymentioning
confidence: 99%
“…Coated pits occur in another mode of internalization characterized by double-membrane invaginations from dendritic spines into presynaptic axons (Westrum and Blackstad, 1962;Andres, 1964;Routtenberg, 1977, 1979;Boyne and Tarrant, 1982;Sorra et al, 1998). This structure has been referred to as the "synaptic spinule" Routtenberg, 1977, 1979) or "spinule complex" (Westrum and Blackstad, 1962).…”
Section: Introductionmentioning
confidence: 99%
“…Data have been obtained [61,62] showing that these "spinules" can be present both in the area of the postsynaptic densities (PSD) and around the periphery of the heads of spines. The possible functions of "spinules" are usually assessed in terms of their contribution to the efficiency of synaptic transmission due to increases in the areas of contacts between the pre-and postsynaptic membranes, especially when new spines form [23,25], though experimental data supporting this role for "spinules" in synaptic transmission have yet to be obtained [61]. We note that in the state of cold-induced torpor in the ground squirrel, when brain electrical activity is minimal, "spinules" penetrating into the presynaptic bouton can also be found on the surfaces of dendritic stems [2,3].…”
mentioning
confidence: 99%
“…Both in organotypic cultures of the hippocampus and in cultures of isolated neurons, de novo synaptogenesis and formation of filopodia occurs virtually constantly, and they may reach lengths of up to 10 µm [15,60,77]. Data have been obtained showing that the hippocampus slices usually used also show synaptogenesis [28,38,55,56,[61][62][63]76]. As demonstrated, comparative analysis of dendritic spines of cultured neurons and intact hippocampus showed that about half the excitatory synapses in vitro are located on dendrites, while in vivo most are located on spines [11].…”
mentioning
confidence: 99%
See 1 more Smart Citation